Software Dalam Tinjauan Akuntansi Berdasarkan SAP No.14 - Fitri, Sri Adella; Putri, Fransisca Aulia; Angrariani, Aprisa; Chantika, Bunga; Aulia, Fauziah (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The development of Government Accounting in Indonesia is lacking in responding to the demands of current developments. The output produced by government accounting in Indonesia cannot be said to be accurate and does not match what it should be, so it cannot be used for decision making. The issuance of Government Regulation no. 71 of 2010 concerning Government Accounting Standards replacing Government Regulation no. 24 of 2005 where this new regulation requires central and regional governments to use accrual-based accounting. Based on this Government Regulation, central and regional governments must use fully accrual-based accounting and not use cash-based accounting that leads to accruals. The aim of this research is to identify how accounting is treated for software at the One-Stop Integrated Services and Manpower Investment Service (PM PTSP and NAKER) based on SAP No. 14 regarding intangible assets. The research method is to use a qualitative method using a descriptive approach by collecting data in the form of observations, interviews and documentation. The results of the research prove that the accounting treatment of software in the Department of Investment, One-Stop Integrated Services and Labor located in Tanah Datar Regency where there is one software, namely SIPINTAR (Taland Datar Licensing Information System), for this SIPINTAR can be identified as an asset. In the form of the service and the acquisition costs for the SIPINTAR software, it meets the provisions of Government Accounting Standards.